1983
DOI: 10.1073/pnas.80.6.1613
|View full text |Cite
|
Sign up to set email alerts
|

Headgroup interactions in mixed phospholipid bilayers

Abstract: 2H NMR methods have been used to study how bilayer-forming phospholipids interact with each other at the membrane surface. Aqueous dispersions of dimyristoyl-sn-phosphatidylcholine (Myr2-PtdCho), dimyristoyl-sn-phosphatidylethanolamine (Myr2-PtdEtn), and dimyristoyl-sn-phosphatidyl-3-glycerol, specifically deuterated at different positions in their headgroups, give well-resolved 2H NMR powder spectra. These spectra are characteristic of a lipid bilayer with quadrupole splittings that are sensitive to the ampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 15 publications
9
32
0
Order By: Relevance
“…A change in the average order parameters of the PC headgroup would be expected to shift both a-and ,B-splittings in the same direction and thus cannot account for the counterdirectional change (Scherer and Seelig, 1989). A similar change in PC headgroup quadrupole splittings has been reported by others investigating effects on membrane surface charge density of various charge carriers including metal ions (Brown and Seelig, 1977;Akutsu and Seelig, 1981;Altenbach and Seelig, 1984;Macdonald and Seelig, 1987), hydrophobic ions (Altenbach and Seelig, 1985), the membrane-bound anion SCN- (Macdonald and Seelig, 1988), charged amphiphiles (Seelig et al, 1987; Scherer and ), the zwitterionic lipophilic molecule phloretin (Bechinger and Seelig, 1991), charged phospholipids (Sixl and Watts, 1983;Scherer and Seelig, 1987), and peptides (Dempsey and Watts, 1987;Dempsey et al, 1989; Kuchinka and Roux et al, 1989; Beschiaschvili and Seelig, 1990a,b). These results have been used to develop a molecular voltmeter model (Scherer and Seelig, 1989) in which membrane-bound ions assert a Coulombic force on the P--N+ dipole of the choline moiety, repelling or attracting the positive nitrogen with respect to the membrane surface, which can cause changes in the conformation of the headgroup and alterations of average C-D bond angles with the molecular axis.…”
Section: Discussionsupporting
confidence: 54%
“…A change in the average order parameters of the PC headgroup would be expected to shift both a-and ,B-splittings in the same direction and thus cannot account for the counterdirectional change (Scherer and Seelig, 1989). A similar change in PC headgroup quadrupole splittings has been reported by others investigating effects on membrane surface charge density of various charge carriers including metal ions (Brown and Seelig, 1977;Akutsu and Seelig, 1981;Altenbach and Seelig, 1984;Macdonald and Seelig, 1987), hydrophobic ions (Altenbach and Seelig, 1985), the membrane-bound anion SCN- (Macdonald and Seelig, 1988), charged amphiphiles (Seelig et al, 1987; Scherer and ), the zwitterionic lipophilic molecule phloretin (Bechinger and Seelig, 1991), charged phospholipids (Sixl and Watts, 1983;Scherer and Seelig, 1987), and peptides (Dempsey and Watts, 1987;Dempsey et al, 1989; Kuchinka and Roux et al, 1989; Beschiaschvili and Seelig, 1990a,b). These results have been used to develop a molecular voltmeter model (Scherer and Seelig, 1989) in which membrane-bound ions assert a Coulombic force on the P--N+ dipole of the choline moiety, repelling or attracting the positive nitrogen with respect to the membrane surface, which can cause changes in the conformation of the headgroup and alterations of average C-D bond angles with the molecular axis.…”
Section: Discussionsupporting
confidence: 54%
“…In the phosphatidylcholine headgroup, the methylene bonded to the oxygen of the phosphate and the adjacent methylene are labeled as a and b, respectively. Counterdirectional shifts in the quadrupole splittings of the aand b-deuterons have been attributed to changes in the orientation of the phosphatidlycholine headgroup with respect to the bilayer normal (Sixl and Watts, 1983;Seelig et al, 1987;Scherer and Seelig, 1989). Incorporation of charged amphiphiles into a bilayer can influence the torque applied to the phosphatidylcholine headgroup electric dipole without substantially perturbing bilayer packing (Seelig et al, 1987;Scherer and Seelig, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…Because a linear correlation exists between the principal values of the 31p chemical shift tensor and the P-O bond length (Un and Klein, 1989), we believe that the small variations in the P-O bond length on protonation or deprotonation will cause small modifications, if any, in the principle tensor values of the H2PO4, H2PO , and pO2groups of DMPA in its three different ionization states. Regarding a change in orientation, it has already been demonstrated that the membrane surface charge density induces conformational changes of the PC headgroup (Sixl and Watts, 1983;Seelig et al, 1987;Scherer and Seelig, 1989). As a result, PCs are already described as behaving like "molecular voltmeters."…”
Section: Discussionmentioning
confidence: 99%